ANALYSIS OF IMPLEMENTATION OF PROMOTION MIX STRATEGY AT HOLIDAY INN EXPRESS BARUNA BALI TO MAINTAIN THE MARKET - Ni Ketut Desi Susantini; I Gusti Putu Sutarma; Ni Luh Eka Armoni (Politeknik Negeri Bali, 2018)
In order to win the competition and to keep the market segment, every hotel should establish the right marketing strategy one of which deals with promotional activities. This study analyzes the implementation of promotion mix strategy at Holiday Inn Express Baruna Bali in maintaining the market. Methods of data collection in this study use non-structured interviews and documentation methods, which became the speakers are the sales and marketing, especially Cluster Sales Executive and Cluster Sales Manager at Holiday Inn Express Baruna Bali. The analytical technique used is qualitative descriptive analysis that is by describing the data that has been collected and analyzed whether the theory of the promotion mix implemented according to existing theory or the company modify the promotion mix startegy. The results showed that the implementation of marketing mix strategy in maintaining the market in Holiday Inn Express Baruna Bali has been applied well.